Solidariedade em movimento: MST E MTST na jornada por um Brasil sem fome - Sá, Maria Emilia Gomes de (Universidade Federal de São Carlos, 2025)
Hunger in Brazil is a persistent social issue, rooted in an economic system that primarily views food as a commodity. To devise solutions for combating hunger, this study focuses on socioterritorial movements as key agents in driving structural transformations within food systems. The proposed project aims to identify and analyze the convergences and differences between the discourses and actions of socioterritorial movements in rural and urban areas, specifically the Movimento dos Trabalhadores Rurais Sem Terra (MST) and the Movimento dos Trabalhadores Sem Teto (MTST), in their fight against hunger. Through a combination of qualitative methodologies, including semi-structured interviews, participant observation, and document analysis, we individually and comparatively examine these social movements based on their discursive dimensions, strategies, and challenges related to overcoming hunger. By analyzing and comparing various forms of food activism in different territories, we identified numerous convergences and some differences between the hunger-combat strategies of the studied socioterritorial movements. The hunger-combat struggles of these movements do not move in opposite directions. Their common goal, centered on deep structural transformations to ensure dignity for workers—through the fight for land, housing, labor, and food—guides the movements toward a shared purpose, which necessarily places the fight against hunger at the heart of their struggles.
Solidarity in movement: MST and MTST in the journey for a hunger-free Brazil
Keywords: Movimentos socioterritoriais; Segurança alimentar; Alianças campo-cidade; Socioterritorial movements; Food security; Rural-urban alliances; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA AGRARIA